2002
DOI: 10.1038/sj.mp.4001074
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide scan shows significant linkage between bipolar disorder and chromosome 12q24.3 and suggestive linkage to chromosomes 1p22–21, 4p16, 6q14–22, 10q26 and 16p13.3

Abstract: The present study reports a genomewide scan using linkage analysis for risk genes involved in bipolar disorder with 613 microsatellite markers including additional testing of promising regions. As previously published significant linkage was obtained at chromosome 12q24.3 with a two-point parametric lod score of 3.42 at D12S1639 including all members in both families (empirical P-value 0.00004, genome-wide P-value 0.0417). The multipoint parametric lod score at D12S1639 was 3.63 (genome-wide P-value 0.0265). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
96
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 67 publications
9
96
1
2
Order By: Relevance
“…The 12q23-q24 region was, however, not reported in meta-analyses of bipolar disorder (Segurado et al, 2003) or schizophrenia . Since the publication of the meta-analyses several further genome scans were published (see Table II) with at least 2 genome scans reporting genome wide significance (Ewald et al, 2002;Shink et al, 2005a, b) within the 12q23-24 region.…”
Section: Discussionmentioning
confidence: 99%
“…The 12q23-q24 region was, however, not reported in meta-analyses of bipolar disorder (Segurado et al, 2003) or schizophrenia . Since the publication of the meta-analyses several further genome scans were published (see Table II) with at least 2 genome scans reporting genome wide significance (Ewald et al, 2002;Shink et al, 2005a, b) within the 12q23-24 region.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were inpatients at the Department of Psychiatry at least once. One hundred and ninety-five patients suffered from schizophrenic disorders according to ICD-10 criteria (56, Figure 1 Based on the chromosomal location built on Ensembl Freeze 04/04, Lod scores of markers on 12q24 are given; the investigated phenotype was either SCZ, [14][15][16][17][18]23 bipolar disorder [5][6][7][8][9][10][11][12]19,22 or major depression. 13 Highlighted are the loci for DAAO, suggested as a candidate gene for bipolar disorder and SCZ, ATP2A2 (the Darier's disease gene) and NOS1.…”
Section: Subjectsmentioning
confidence: 99%
“…3,4 A further consistently identified locus for endogenous psychoses, usually with Lod scores between 2 and 3, is located on 12q22-24. BPD has been replicated 8 times, [5][6][7][8][9][10][11][12] but also major depression (MD) was linked to this locus with a very high Lod-score > 6, which might be due to the homogeneity of the sample consisting of 110 pedigrees from Utah. 13 SCZ and schizoaffective disorder [14][15][16][17] and the marker 'negative symptoms' in SCZ 18 linked to 12q22-24 as well.…”
Section: Introductionmentioning
confidence: 99%
“…39 The second focus of findings (F-2) is at 105 Mb, mainly in BPD, with one significant study 42 and several supporting studies, 37,38,46 but also studies on SCZ, 24 autism 52 and multiple sclerosis. 53 The third focus (F-3) is for BPD and is located at 126 Mb with a very significant finding from one study of Portuguese pedigrees.…”
Section: Discussionmentioning
confidence: 99%
“…45 The fourth focus (F-4) is centered at 136 Mb, with significant findings in SCZ-related disorders coming from one linkage study 31,32 and one association study, 14 and weak support from other studies in SCZ. 26,39 Support for this focus also comes from linkage and association studies in BPD 38,48,49 and from a meta-analysis of linkage studies in BPD 5 as well as from the presence of AHI1, a gene causing a severe neuropsychiatric disorder (Joubert Syndrome) in this location. Weaker positive results in linkage studies of SCZ and BPD were also demonstrated distal to this focus 28,40,47 and may represent poorer localization of the same locus.…”
Section: Discussionmentioning
confidence: 99%